The Effectivity of Extracts Soybean on Increasing Concentration of RBP (Retinol binding protein) in White Rat (Rattus norvegicus) Kwashiorkor Model - Rizsa Aulia Danesty; Heni Fatmawati; Angga Mardro Raharjo (Journal of Agromedicine and Medical Sciences, 2017)
Kwashiorkor is a disease caused by a deficiency of protein in terms of both quality and quantity. Kwashiorkor cause dysfunction in various organ systems. The purpose of this study was to determine the role of soy in increasing serum RBP levels in rat models of kwashiorkor. The liver is a vital organ for protein synthesis, one RBP. The liver is particularly vulnerable to the effects of kwashiorkor. The method used is the mice given low-protein diet for 30 days and then given extract of soybean meal for 30 days subsequent serum RBP levels were evaluated using ELISA method. The results showed that the soy extract can increase the levels of RBP in mice models of kwashiorkor. Keywords: RBP, soybean extracts and kwashiorkor